Isomorfisme Institusional Pada Pengungkapan SDGs Didalam Sustainability Reporting - Wisnu Setyawan; Nanny Dewi Tanzil; Dini Rosdini (Jurnal Riset Akuntansi dan Keuangan, 2023)
Based on the institutional isomorphism theory approach, this study aims to examine the impact of government policies as a coercive factor, as well as the role of CSR governance and the concept of corporate sustainability strategic management as normative factors for organizational change regarding compliance and appropriateness of SDGs disclosure in sustainability reports (SR). Using secondary data from 231 company SRs which operating in Indonesia for the reporting period 2018-2020, obtained 136 SRs that meet the research sample criteria, and then processed by testing statistical regression analysis. The results of this study indicate that the level of disclosure of corporate support for SDGs in SR is influenced by CSR governance and corporate sustainability strategic management.